Inspiring urology trainees to enter academic careers - Gabriel P Haas (Indian Journal of Urology, 2009)
The physician-scientist in academic medical centers has been called as ′an endangered species′. Adverse socioeconomic pressures, lack of dedicated research time, and increasing difficulties in obtaining grant support, make it more and more difficult to attract talented individuals for this career path, and consequently to recruit and retain them in the urology departments. The challenges facing the young academic faculty, physician-scientists, and the research trainees represent a danger to the future of academic medicine. Only a concerted effort to balance the financial disincentives, providing a protected time, a nurturing environment, and the emphasis on outstanding mentors and role models, can secure the continued research and academic success of urology programs. The disproportionate representation of women and the minorities among academic faculty must be recognized and addressed.